Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. A proposed vision for the role of Saudi universities in developing and enhancing the intellectual security of their studentsDr. Aisha Ali Msoud Asiri2. The Degree of Application of Administrative Accountability among Government School principals in the schools of the Yatta Directorate of Education from the point of view of TeachersMr. Ibrahim Musallam Makhamreh, Ms. Rasha Yasser Alyan3. Digital transformation in the use of artificial intelligence in education for smart schools  in Jenin GovernorateMs. Inas Fuad AbuFarhah, Dr. Maher Fuad AbuFarhah4. Scientific parks in some countries and the possibility of benefiting from them  in the Kingdom of Saudi ArabiaMs. Hanan Nour Al-Solami, Co-Prof. Mona Muhammad Alsanee5. The criteria for nominating gifted coordinators in public and private schools and their effects  on talent sustainability: A mixed studyMs. Albandary Abdullah Alhassan, Dr. Abdulhamid Alarfaj6. Developing the leadership competencies of department heads in Saudi universities in light of the human capacity development programMr. Ali Yahya Garrah7. The relationship of quality of life to the level of ambition in light of some variables among students at the College of Educational Sciences, Mu’tah UniversityMr. Fahd Hamad Al-Nuaimi8. Requirements for the Implementation of Cyber Security in Nizwa University in light of Oman Vision 2040 and its obstacles from the point of view of academics and employeesMs. Najla Moosa Mohammed Al-Balushi, Ms. Teeba Saif Ahmed Al-Rawahi, Ms. Badriya Hamood Said Al-Aamri,  Dr. Rabia Al-Mur Ali Al-Dhuhli, Dr. Hamed Hilal Hamood Al-Yahmadi, Dr. Mohammed Ismail Abdullah Al-Qudah
Keywords: Journal of Educational and Psychological Sciences